ORMDL3 Functions as a Negative Regulator of Antigen-Mediated Mast Cell Activation via an ATF6-UPR-Autophagy–Dependent Pathway - Li, Jia; Ullah, Md Ashik; Jin, Hongping; Liang, Yuting; Lin, Lihui; Wang, Juan; Peng, Xia; Liao, Huanjin; Li, Yanning; Ge, Yiqin; Li, Li (Frontiers in Immunology, 2021)
Antigen (Ag)-mediated mast cell activation plays a critical role in the immunopathology of IgE-dependent allergic diseases. Restraining the signaling cascade that regulates the release of mast cell-derived inflammatory mediators is an attractive therapeutic strategy to treat allergic diseases. Orosomucoid-like-3 (ORMDL3) regulates the endoplasmic reticulum stress (ERS)-induced unfolded protein response (UPR) and autophagy. Although ERS/UPR/autophagy pathway is crucial in Ag-induced mast cell activation, it is unknown whether ORMDL3 regulates the ERS/UPR/autophagy pathway during mast cell activation. In this study, we found that ORMDL3 expression was downregulated in Ag-activated MC/9 cells. Overexpression of ORMDL3 significantly inhibited degranulation, and cytokine/chemokine production, while the opposite effect was observed with ORMDL3 knockdown in MC/9 cells. Importantly, ORMDL3 overexpression upregulated mediators of ERS-UPR (SERCA2b, ATF6) and autophagy (Beclin 1 and LC3BII). Knockdown of ATF6 and/or inhibition of autophagy reversed the decreased degranulation and cytokine/chemokine expression caused by ORMDL3 overexpression. Moreover, in vivo knockdown of ORMDL3 and/or ATF6 enhanced passive cutaneous anaphylaxis (PCA) reactions in mouse ears. These data indicate that ORMDL3 suppresses Ag-mediated mast cell activation via an ATF6 UPR-autophagy dependent pathway and thus, attenuates anaphylactic reaction. This highlights a potential mechanism to intervene in mast cell mediated diseases.